Theoretical and methodological loyalty management approaches in the conditions of digital transformation - Holovan, Olha; Oliinyk, Oleksandr; Markova, Svitlana; Oliinyk, Maksym (Management and Entrepreneurship: Trends of Development, 2024)
The conditions of digital transformation require from loyalty management a deep understanding of customer needs, individualization of interaction, use of advanced technologies and analytical methods. On this basis, companies form effective strategies for loyalty management, helping to strengthen their positioning in the market and ensuring a stable level of income in the future. The article determines that the formation of customer loyalty depends on various factors that affect trust in the company and its products. The key factors influencing the formation of loyalty are positive experience of the client’s interaction with the company; recommendations from relatives and friends; charitable or social activities of the company; as well as information about the company (brand) in social networks, etc. Trade marketing is one of the forms of modern marketing aimed at developing and maintaining partnership relations, increasing brand recognition, increasing sales volumes and building consumer loyalty. Trade marketing tools to form customer loyalty include discount programs, accumulative discount cards, cashback, gift certificates, gift lotteries, bonus incentive programs, loyalty clubs and merchandising tools. To implement the company’s loyalty management strategy, it is necessary to clearly define the loyalty management strategy, taking into account the company’s goals, available material and informational resources; to identify the target consumer segments for the company; to conduct research of the consumer behavior motives and their attitude towards the brand/company; to determine criteria for evaluating consumer loyalty and evaluation frequency; to develop a system of forming a positive customer experience through personalization of offers and service individualization; to create a system of feedback and prompt response to requests, taking into account digital transformation; to analyze the effectiveness of loyalty programs and communication tools with customers. JEL класифікатор: D12, L81, M10, М31